Analysis of the Economic Well-being of Traditional and Modern Fishermen from an Islamic Economics Perspective (Case Study of Asembakor Village, Kraksaan, Probolinggo) - himmah, Mufidatul; Hatami, Muhammad Rojhil Ghufron (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2026)
This study aims to analyze the economic well-being of traditional and modern fishermen in Asembakor Village, Kraksaan, Probolinggo, using an Islamic economics perspective. The phenomenon observed is a disparity in well-being between these two groups of fishermen, which is linked to differences in technology use and market access. The main issue in this study is how Islamic economics can be applied to improve the well-being of fishermen, both economically and socially. The method used in this study is a qualitative approach using a case study design. Data were collected through in-depth interviews, participatory observation, and documentation. Research informants consisted of traditional fishermen, modern fishermen, and other community leaders. The data analysis technique used was thematic analysis, which allowed the researcher to identify patterns from the collected data and relate them to Islamic economic theory. The results of the study indicate that modern fishermen have higher incomes and broader market access, yet they often disregard sustainability principles in the utilization of natural resources. Meanwhile, although traditional fishermen have lower incomes, they pay more attention to social and sustainability aspects in the management of their catch. This study concludes that the application of Islamic economics in the fisheries sector can help create more equitable and sustainable welfare for fishermen. The implications of this study highlight the importance of policies supporting technology integration for traditional fishermen as well as the application of Sharia economic principles in fisheries sector policies. A recommendation for future research is to examine the implementation of Sharia economics in other regions with different social and economic characteristics.